2011
DOI: 10.1097/prs.0b013e31821741ed
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Healing of Human Cutaneous Surgical Incisions Created by the PEAK PlasmaBlade, Conventional Electrosurgery, and a Standard Scalpel

Abstract: Therapeutic, II.(Figure is included in full-text article.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 20 publications
7
78
0
Order By: Relevance
“…The LTD used in this study has previously been shown to significantly decrease the depth of thermal injury during dissection of skin and fascia in clinical and preclinical studies, minimizing collateral tissue damage, and providing a healing profile equivalent to scalpel. [14][15][16][17][18][19] This LTD has also been shown to reduce scarring and wound necrosis 20 as well as to improve surgery time, hospital stay, and cost in select applications. 21 This LTD has not yet been assessed in ACDF; thus, this pilot study was designed to evaluate and compare its properties with ES in a cadaveric model.…”
Section: Discussionmentioning
confidence: 99%
“…The LTD used in this study has previously been shown to significantly decrease the depth of thermal injury during dissection of skin and fascia in clinical and preclinical studies, minimizing collateral tissue damage, and providing a healing profile equivalent to scalpel. [14][15][16][17][18][19] This LTD has also been shown to reduce scarring and wound necrosis 20 as well as to improve surgery time, hospital stay, and cost in select applications. 21 This LTD has not yet been assessed in ACDF; thus, this pilot study was designed to evaluate and compare its properties with ES in a cadaveric model.…”
Section: Discussionmentioning
confidence: 99%
“…This feature of the device is presented as a factor which reduces tissue ischemia. 13 Ischemia-modified albumin (IMA) has emerged as a sensitive biomarker in the evaluation of tissue ischemia, and was used in many ischemic conditions such as myocardial ischemia, skeletal muscle ischemia, pulmonary embolism, and stroke. [13][14][15][16] To the best of our knowledge, there are no studies showing whether this increases after axillary dissections during mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma creates an electrically conductive cloud when radiofrequency energy contacts tissue [9]. An advantage of PlasmaKinetic is cutting the tissues at a much lower average temperature (as low as 50°) than conventional electrocautery [10]. As a result of this, thermal damage of the surrounding tissue is less than 1 mm.…”
Section: Discussionmentioning
confidence: 99%